Di bụ ugwu nwanyị (Husband is the dignity of a woman): Reimagining the Validity of an Igbo Aphorism in Contemporary Society - Wariboko, Onyinyechi Priscilla Christian; Mbonu, Caroline N. (Journal of Gender and Power, 2021)
Cultural aphorisms tend to sustain gender disparity. There are certain cultural expressions which tend to sustain gender disparity and oppression among the Igbo of Nigeria. One of such is di bụ ugwu nwanyị, literally translated ‘husband is a woman’s dignity’. This Igbo maxim tends to foster gendered marginalization and oppression in contemporary Igboland. The saying reinforces the status of the husband as requisite for the visibility and pride of the woman. Perhaps this may explain why some marital issues such as husband infidelity, wife-battering, are culturally underplayed for protection of the man. Thus women are forced to endure abuses in their marriages. There exist a plethora of other gender related issues that are rooted in the di bụ ugwu nwanyị metaphor. This paper engages the implications of this Igbo cultural expression amidst the advocacy of gender justice and inclusivity in Igbo land. As qualitative study that adopts the phenomenological approach, this paper, draws insight from interviews, observations, oral histories and extant Igbo literature. Akachi Ezeigbo’s snail-sense feminism and Obioma Nnaemeka’s negofeminism undergird the theoretical framework. The paper advocates for the obliteration, or reinterpretation of di bụ ugwu nwanyị that honours dignity for gender equity and inclusivity so as to valorize the status of women in Igboland.